2023
DOI: 10.1021/acsanm.3c01396
|View full text |Cite
|
Sign up to set email alerts
|

Dual Linear Range Laser-Induced Graphene-Based Sensor for 4-Nitrophenol Detection in Water

Abstract: Electrochemical sensors provide an excellent platform for in situ water pollutant detection. Graphene-based electrochemical sensors have been effective in the analysis of different genres of pollutants. However, the complex, chemically intensive steps of graphene fabrication and its modification pose challenges to the large-scale application of these sensors. Laser-induced graphene (LIG) is a promising technology with a simple, rapid, chemical-free, mask-free, and scalable solution to produce graphene-based el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Figure presents CV scans of PMA2TA, PMA2TA@g-C 3 N 4 , sPMA2TA, and sPMA2TA@g-C 3 N 4 electrocatalytic materials. In general, the anodic peak current ( I pa ) increases with the increasing scan rate (ν), which manifests the diffusion-limiting electrochemical redox reactions at the electrode surface. , The respective plots of I pa vs ν 1/2 , shown in Figure (insets), also illustrate a linear relationship over the range of the employed scan rates. The corresponding regression equations for each electrode are given below…”
Section: Resultsmentioning
confidence: 87%
“…Figure presents CV scans of PMA2TA, PMA2TA@g-C 3 N 4 , sPMA2TA, and sPMA2TA@g-C 3 N 4 electrocatalytic materials. In general, the anodic peak current ( I pa ) increases with the increasing scan rate (ν), which manifests the diffusion-limiting electrochemical redox reactions at the electrode surface. , The respective plots of I pa vs ν 1/2 , shown in Figure (insets), also illustrate a linear relationship over the range of the employed scan rates. The corresponding regression equations for each electrode are given below…”
Section: Resultsmentioning
confidence: 87%
“…The electrodes were modified with tungsten disulfide nanosheets/hydroxylated multi-walled CNTs (WS2/MWCNTs-OH) for enhanced sensitivity. A recent study reported the development of laser-induced graphene printed on polyimide films for 4-nitrophenol detection in water [ 84 ]. The presence of 4-nitrophenol induced a cyclic voltammetry response that corresponded to the concentration of 4-nitrophenol.…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…The sensor displayed good selectivity for 4-NP, even in the presence of isomers and other phenolic compounds and in sewage samples with different 4-NP concentrations. 206 …”
Section: Transduction Mechanisms Of Gr-based Electroanalytical Devicesmentioning
confidence: 99%